Spatial Correlation of Radio Waves for Multi-Antenna Applications in Indoor Multipath Environments - Hendrantoro, Gamantyo; Handayani, Puji; Mauludiyanto, Achmad (Institute of Research and Community Outreach, 2007)
This paper presents the results of a concerted effort in characterizing the spatial correlation of radio waves detected by a multi-element antenna system in indoor environments. The number of arriving paths and their directions are first studied through a series of measurements. The results are then used in a simulation to obtain spatial correlation indoors. It is found that generally an antenna array positioned near the center of the room will experience more rapidly decreasing correlation with spacing, which is a desired trait. In addition, a linear array oriented perpendicular to the length of the room in general shows better characteristics in terms of faster slope of correlation compared to the one in parallel with the length of the room. The average correlation indoors is also found to be similar to the correlation function arising from the two-dimensional circularly distributed random scatterers proposed by Clarke. For practical implementation of antenna arrays in small terminals for indoor wireless applications, it is suggested that the inter-element spacing be made 0.3? in the least.